Column experiment reveals high natural attenuation potential for toluene in iron-rich aquifers but significant concomitant secondary Fe pollution risk - Zhang, Min; Di, He; Wang, Shuaiwei; Ning, Zhuo (Frontiers in Microbiology, 2025)
IntroductionIron mineral reduction mediated by indigenous microbes represents a crucial natural attenuation mechanism for organic contaminants like toluene in anaerobic aquifers, yet the partitioning of generated Fe(II) species and associated secondary pollution risks remain poorly constrained.MethodsThis study employed controlled column experiments simulating an iron-rich aquifer (ferrihydrite-amended quartz sand) to track the biogeochemical dynamics of toluene degradation coupled with iron transformation. Over 43 days, we quantified spatiotemporal changes in toluene concentrations, dissolved/solid-phase iron species, and microbial community structure through high-frequency hydrochemical monitoring and metagenomic sequencing.Results and discussionResults demonstrated that iron-reducing consortia (notably Thiobacillus and Pseudomonas) drove > 99% toluene degradation within 10 cm flow distance, effectively containing plume migration. However, Fe(III) reduction generated Fe(II) predominantly (98%) as immobile solid-phase minerals, with only 1%–2% manifesting as dissolved Fe2+. This dissolved fraction accumulated progressively across space and time, exceeding China’s groundwater quality threshold (0.3 mg/L) at 90% of monitoring points by experiment termination despite near-complete toluene removal. The study confirms that iron-rich aquifers provide significant natural attenuation capacity for petroleum hydrocarbons but concurrently pose substantial secondary contamination risks through highly mobile Fe2+ generation. Therefore, it is recommended to include solidphase ferrous iron [Fe(II)] as an indicator in natural attenuation assessments and to take into account biogeochemical by-products such as Fe2+ in risk assessment efforts.